Three Japanese patients with congenital pituitary hormone deficiency and ophthalmological anomalies - Kuniko Takanashi; Yashuto Suzuki; Ayumu Noro; MInako Sugiyama; Masanori Nakanishi; Tetsuro Nagashima; Akie Nakamura; Ishizu Katsura; Toshihiro Tajima (MDPI AG, 2011)
The clinical phenotype of congenital pituitary hormone deficiency is variable and can be associated with a number of structural abnormalities of the central nervous system. We report three Japanese patients with congenital pituitary hormone deficiency and ophthalmological anomalies. Two of the patients initially showed strabismus and unilateral optic nerve hypoplasia. Thereafter, growth failure became evident, leading to the diagnosis of pituitary hormone deficiency. The other patient had severe congenital hypopituitarism with respiratory distress and hypoglycemia from the first day of life. In addition, he had prolonged jaundice and impaired liver function with bilateral optic nerve hypoplasia. Neuroimaging of the pituitary region in all three patients demonstrated a small anterior pituitary lobe and no pituitary stalk. Our findings indicate that clinical variability of congenital hypopituitarism must be considered. In a patient with ophthalmological symptoms, endocrine evaluation and neuroimaging of the CNS including the pituitary region should be considered.